Visual semiotics of ENHYPEN’s Bite Me from the Dark Blood album in shaping brand image - Wardaya, Marina; Allen, Natania Edelynn Fidelia (Universitas Indraprasta PGRI, 2025)
Over time, K-pop has grown and emerged as a global music phenomenon, with visual elements functioning not only as enhancements but also as strategic elements of building brand identity and contributing to global success. The purpose of the study presented here is to investigate the significance of visual semiotics within K-pop by conducting an analysis of the integrated marketing communication (IMC) efforts of one artist via a single-case study. Specifically, this research focuses on ENHYPEN's Bite Me from their album Dark Blood, using visual examples found in promotional material (teasers, music videos, and physical albums) to illustrate how visual elements work together to create a unified brand image based upon dark romance aesthetics. The methodology used was descriptive qualitative analysis, with Roland Barthes' semiotic theory being applied to identify patterns in visual semiotics through the use of imagery, typography, colour schemes, choreography, and spatial planning. According to the research, common customized serif will reinforce how visual language creates meaning through visuals for the following themes: loyalty, desire, transformation, and destined love. each symbol include: black, red, & blue (colors); blood (vampire images); moon (vampire imagery); coffin (vampire imagery) this creates mythical elements which build an ideology of eternal and dangerous love, which supports the image of ENHYPEN in relation to dark romanticism contemporary K-pop culture. the study also demonstrates that layered visual narratives exist across many types media based upon consistent visual aesthetics (visual storytelling), and ongoing storytelling (consistency), and all these have an energetic connection to building an emotional connection with fans when competing for long-term fan loyalty in the global music industry.